2011
DOI: 10.1172/jci59981
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α6β4 identifies an adult distal lung epithelial population with regenerative potential in mice

Abstract: The dosage for GW9662 was incorrectly noted in Results, Methods, and the legend for Figure 6. The correct sentences appear below.Results: We treated a cohort of younger animals for 2 weeks at a dose of 4 mg/kg body weight and found that there was a 31% reduction in the expression of Cd36 ( Figure 6F) and a 48% reduction in liver TG content in JAK2L animals treated with GW9662 versus those treated with vehicle ( Figure 6G). Methods: Each day, an aliquot of stock drug was thawed and then resuspended in DMSO/sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(177 citation statements)
references
References 0 publications
10
167
0
Order By: Relevance
“…2B, upper right) and few if any for the Clara cell marker CCSP. This phenotype matches a progenitor cell phenotype recently reported in adult murine lungs (25). In four independent experiments, cell lines emerging from culture of AECs isolated from mice expressing large T antigen highly expressed ␣6␤4 and were largely deficient in type II or Clara cell lineage markers.…”
Section: D and C Lower)supporting
confidence: 86%
“…2B, upper right) and few if any for the Clara cell marker CCSP. This phenotype matches a progenitor cell phenotype recently reported in adult murine lungs (25). In four independent experiments, cell lines emerging from culture of AECs isolated from mice expressing large T antigen highly expressed ␣6␤4 and were largely deficient in type II or Clara cell lineage markers.…”
Section: D and C Lower)supporting
confidence: 86%
“…These cells comprise B10% of all lung cells, express little or no CC10 and SpC, but they are able to give rise to the differentiated airway and alveolar cells. 19,20 To delete the transcriptional termination cassette (Lox-StopLox) and thus activate the expression of the KrasG12D protein, we used a self-excising retroviral vector expressing Cre recombinase. 23 The presence of the activated KrasG12D allele was confirmed by western blot analysis of KrasG12D and total Kras expression (Figure 1b), and by detection of active GTPbound Kras protein (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…12,14,17 However, to date, only AT2 cells have been conclusively identified as having the potential to be the cells of origin for lung ADC. 14,17 This raises the question of whether Clara cells, their restricted subpopulations or the newly identified candidate stem cells, termed distal airway stem cells, 18 alveolar epithelial progenitor cells (AECs) 19,20 and BASCs, 12 also have the capacity to give rise to ADC. Current knowledge on the cellular origins of SCC, the second most common type of lung cancer, lags behind that of ADC, partly owing to the fact that squamous cells are not normally present in the respiratory epithelium, and therefore arise through either metaplasia (conversions between stem cell states) or trans-differentiation (conversions between differentiated cells).…”
mentioning
confidence: 99%
“…Parallel studies, and the refinement of cell separative strategies used by other laboratories, have since shown that candidate stem/progenitor cells isolated from different regions along the proximodistal lung axis share a similar if not identical biomarker repertoire. These include bronchioalveolar stem cells (BASCs) (24), bronchiolar progenitor cells (25), and multipotent a6 pos b4 pos cells, recently shown to recapitulate lung morphogenesis in a sub-kidney capsule lung organoid transplant assay (26). Dr. Bertoncello argued that although this reductionist approach provides powerful tools to monitor the status of stem/ progenitor pools in the normal and diseased lung, and to identify regulatory factors, cytokines, and pathways that specify their fate, much still remains to be done to precisely understand what these assays are telling us about the organization, regulation, and regenerative potential of endogenous lung stem cells in situ.…”
Section: Clinicalmentioning
confidence: 99%